An Analysis of the Oral Communication Barriers in Face-to-face Communications Towards the Development of an Intervention Program in Speaking - Ayawan, Jessica E.; Duyapat, Novelia O.; Martin, Alexa B. (Technium Social Sciences Journal, 2022)
This study aimed to unravel the speaking barriers experienced by the criminology students in face-to-face oral communications, the effects of these barriers in their speaking performance and the strategies they use to cope with these speaking barriers. Results from these queries served as bases in developing a remedial intervention program that aims to improve students’ English-speaking skills and overcome their communication barriers most specially in face-face-to settings. To achieve these aims, this study used qualitative descriptive design with semi-structured interview as data gathering tool. Nine criminology students were interviewed. Results showed that the oral communication barriers experienced by these 9 criminology students in face-to-face communications with English as medium include lack of knowledge of the English language such as vocabulary, grammar, and pronunciation; limited content knowledge/topical knowledge; and psychological related constraints. Meanwhile, results showed that the oral communication barriers experienced by the criminology students result to misinterpretation of the meaning they want to convey and mental blackouts. Findings also showed that the participants employ strategies in coping with the oral communication barriers and in avoiding being misinterpreted and mental blackouts, these include watching English movies, reading, practicing oneself to speak in English alone, googling, and interacting with others.